(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The problems of studying the so called «stateiny records» are considered in the article. Being the monuments of business writing of the Old Russian literature of the XVI-XVII centuries they have attracted the attention of historians during the long time but have been little studied by philologists – linguists and literary critics. The review of scientific literature – historical, linguistic, literary – devoted to these texts is provided in this article. The necessity of philological analysis of the stateiny records in terms of modern linguistic paradigms is also substantiated in this article.